Immunoseq: the identification of functionally relevant variants through targeted capture and sequencing of active regulatory regions in human immune cells. Issue 1 (December 2016) - Morin, Andréanne; Kwan, Tony; Ge, Bing; Letourneau, Louis; Ban, Maria; Tandre, Karolina; Caron, Maxime; Sandling, Johanna; Carlsson, Jonas; Bourque, Guillaume; Laprise, Catherine; Montpetit, Alexandre; et al.
Abstract Background The observation that the genetic variants identified in genome-wide association studies (GWAS) frequently lie in non-coding regions of the genome that containcis- regulatory elements suggests that altered gene expression underlies the development of many complex traits. In order to efficiently make a comprehensive assessment of the impact of non-coding genetic variation in immune related diseases we emulated the whole-exome sequencing paradigm and developed a custom capture panel for the known DNase I hypersensitive site (DHS) in immune cells – "Immunoseq". Results We performed Immunoseq in 30 healthy individuals where we had existing transcriptome data from T cells. We identified a large number of novel non-coding variants in these samples. Relying on allele specific expression measurements, we also showed that our selected capture regions are enriched for functional variants that have an impact on differential allelic gene expression. The results from a replication set with 180 samples confirmed our observations. Conclusions We show that Immunoseq is a powerful approach to detect novel rare variants in regulatory regions. We also demonstrate that these novel variants have a potential functional role in immune cells.